The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1111/j.1476-5381.1975.tb07356.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cocaine and Sodium on Bretylium Uptake by Reserpine‐treated Guinea‐pig Left Atrium

Abstract: 1The effects of cocaine and sodium on bretylium uptake into sympathetic nerve terminals were investigated in the reserpine-treated guinea-pig left atrium. The ability of bretylium pretreatment to increase the retention of noradrenaline was used as an index of bretylium uptake. Such increased retention has been assessed both by direct measurement and by the ability of tyramine to produce an inotropic response. 2 The restoration of the response to tyramine after incubation with noradrenaline was abolished when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The uptake of [3H]NA was more prominent in P1 segments (proximal to the ligature) that in DI segment (distal to the ligature) and seems to be very specific, since cholinergic nerves and fragments of peritoneum, of weight and size similar to hypogastric nerves, took up and retained [3H]NA in much smaller amounts and this uptake was not blocked by cocaine. Reserpine not only decreased the NA content ofnerves but also diminished the net uptake of [3H]NA, probably by reducing its retention, as a consequence of intraneuronal deamination by monoamine oxidase as occurs in other tissues (Furchgott & Sanchez-Garcia, 1968;Garcia & Sanchez-Garcia, 1975). Our results also show that 6-hydroxydopamine, after collagenase treatment of nerves, markedly decreased the net uptake of [3H]NA.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The uptake of [3H]NA was more prominent in P1 segments (proximal to the ligature) that in DI segment (distal to the ligature) and seems to be very specific, since cholinergic nerves and fragments of peritoneum, of weight and size similar to hypogastric nerves, took up and retained [3H]NA in much smaller amounts and this uptake was not blocked by cocaine. Reserpine not only decreased the NA content ofnerves but also diminished the net uptake of [3H]NA, probably by reducing its retention, as a consequence of intraneuronal deamination by monoamine oxidase as occurs in other tissues (Furchgott & Sanchez-Garcia, 1968;Garcia & Sanchez-Garcia, 1975). Our results also show that 6-hydroxydopamine, after collagenase treatment of nerves, markedly decreased the net uptake of [3H]NA.…”
Section: Discussionsupporting
confidence: 72%
“…It is well known that cocaine blocks NA uptake by noradrenergic nerve terminals (see MacMillan, 1959;Whitby et al 1960;Muscholl, 1961;Iversen, 1967;Furchgott & Sanchez-Garcia, 1968;Garcia & Sanchez-Garcia, 1975). The results of the present experiments also showed that cocaine markedly diminished the [3H]NA uptake both in unligated and ligated hypogastric nerve trunks but not in vagus nerve and peritoneum, indicating that the uptake of [3H]NA into the sympathetic nerve takes place through a carrier similar to the U1 uptake system described in the nerve terminals.…”
Section: Presence Of An Na Carrier In Ligated Nervesmentioning
confidence: 99%
See 2 more Smart Citations
“…The uptake was saturable with an apparent Km of 3 x 10-6 M. The uptake was inhibited by amphetamine, norepinephrine, desmethylimipramine, cocaine, guanethidine, low sodium and ouabain. GARCiA and SANCHEZ-GARCiA (1975) using indirect methods studied the uptake of bretylium in reserpine-treated, guinea-pig atria. Cocaine and low sodium greatly reduced the retention of bretylium.…”
mentioning
confidence: 99%